ROLE-PLAY AND SHOW-AND-TELL IN GRADE 5 STUDENTS' SPEAKING LEARNING - Choiril Anwar (Universitas Islam Sultan Agung, 2016)
This research aimed to investigate (1) the effectiveness of role-play and show-and-tell, and (2) which one was more effective between role-play and show-and-tell in grade 5 students’ speaking learning. It was an experimental study by randomized pretest-posttest control group design. The data were collected by a non-test of an observation. The instrument of the research was observation sheets completed by speaking rubric onLikert scale. The data were analyzed by using one-way ANOVA followed by the Scheffe test. The results of the research showed that: (1) role-play and show-and-tell were effective in grade 5 students’ speaking learning indicated by p < 0.05 and; (2) role-play was more effective than show-andtell indicated by p < 0.05.